Large Angle Bending Behavior of Curved Members Using The Method of Characteristics - Al-Da’ami, Haitham H.; Al-Rajihy, Ahmed A.; Fadhel, Essam Z. (Al-Khwarizmi Engineering Journal, 2019)
This paper deals with the nonlinear large-angle bending dynamic analysis of curved beams which investigated by modeling wave’s transmission along curved members. The approach depends on the wave propagation in one-dimensional structural element using the method of characteristics. The method of characteristics (MOC) is found to be a suitable method for idealizing the wave propagation inside structural systems. Timoshenko’s beam theory, which includes transverse shear deformation and rotary inertia effects, is adopted in the analysis. Only geometrical non-linearity is considered in this study and the material is assumed to be linearly elastic. Different boundary conditions and loading cases are examined. From the results obtained, it is found that the geometrical shape, boundary conditions, material properties of the members as well as the load type and direction have considerable effects on the response of the member.